Proceso atención de enfermería en preescolar con diagnóstico de meningitis. - Guillen Ortiz, Digna Juleidy (2024)
This case report presents the nursing care process in a preschooler diagnosed with meningitis, which begins with a thorough assessment of the patient, including the collection of relevant data through the medical history and the identification of characteristic symptoms, such as fever, neck stiffness, headache, irritability, vomiting and photophobia. The nursing role is based on the exhaustive assessment of the patient, being an essential piece for the establishment of a solid basis for the diagnosis and care plan. The above mentioned, goes hand in hand with a good physical examination that allows us to know the signs and symptoms through significant data through the patient's medical history. From this initial assessment that helped us to establish priorities and personalized nursing care objectives. Based on the nursing care plan, it should be taken into account that the continuous monitoring of vital signs is fundamental, as well as the emotional support to both the child and his family, who have agreed to the hospital admission and have shown willingness for the treatment, which is based on the administration of drugs prescribed by the doctor on duty, continuously assessing the response to it. Therefore, the aforementioned nursing care plays a fundamental role in the child's state of health, contributing to its improvement through the careful follow-up of the care plan to observe if the care should be modified based on the patient's needs to improve the results seeking the improvement of the patient's state of health, demonstrating the effectiveness of this plan applied to witness the recovery of the preschooler with a diagnosis of meningitis.